Buddhism for western children - Allio, Kirstin (Book collections on Project MUSE., 2018)
Set on the coast of Maine and in the high desert of New Mexico in the late 1970s through the early 80s, Buddhism for Western Children is a universal and timeless story of a boy who must escape subjugation, tell his story, and reclaim his soul.